Consumer anxiety: A scoping review and research agenda - Mingfei Li; Shanshan Huang (PLoS ONE, 2026)
Background In the current vibrant and transforming era, consumers increasingly experience anxiety. Given its profound implications for consumers’ psychological well-being, decision-making, and consumption behaviors, understanding consumer anxiety (CA) has become a critical issue for both scholars and practitioners. Although existing studies have investigated CA across contexts, the findings remain both limited and fragmented. Objective To provide a comprehensive and clearer picture of CA, this scoping review synthesizes the current state of the art in CA research, develops an integrative research framework, and outlines promising avenues for future inquiry. Method Following the Systematic Reviews and Meta-Analyses (PRISMA) guidelines, this study searched Google Scholar, ScienceDirect, EBSCO, and the Social Science Citation Index for articles. After study selection and quality assessment, 60 articles focusing on CA were identified and included in the review. Results Current research elucidates the antecedents and consequences of CA, as well as its mediating and moderating roles in consumer studies. Conclusion On the basis of the reviewed findings, this study discusses the research gaps and thereby proposes promising avenues for future CA research. Moreover, several valuable insights for CA management are provided for practitioners in the marketplace.